The Impact of Globalization on Leadership and Governance in Mali - Traore, Souleymane (International Journal of Leadership and Governance, 2023)
Purpose: The study sought to analyze the impact of globalization on leadership and governance in Mali Materials and Methods: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that globalization has had a profound impact on leadership and governance in the world today. Globalization is a complex and multifaceted phenomenon, and its effects can be seen in virtually every sector of society. From economic and political systems to social and cultural norms, globalization has altered the way in which we view and interact with the world. Unique Contribution to Theory, Practices and Policies: The functionalism theory, realism theory and constructivism theory may be used to anchor future studies in the leadership and governance sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management of private and public industries in the country will also use the study findings to improve leadership and governance performance in all their activities and programs. The study recommends that the adoption of effective development policies in the leadership and governance will help to improve efficiency in their major operations and activities.